Ovarian response and embryo production in llamas treated with equine chorionic gonadotropin alone or with a progestin-releasing vaginal sponge at the time of follicular wave emergence - Huanca López, Wilfredo (2009)
The objective of the study was to compare the ovulatory response and embryo production in llamas (Lama glama) treated with a single dose of equine chorionic gonadotropin (eCG) alone or combined with intravaginal medroxyprogesterone acetate (MPA) at the time of follicular wave emergence. Llamas with a growing follicle ≥7 mm in diameter were assigned to one of the following groups: (1) Control (n = 28): Nonstimulated llamas were mated and embryos were collected 7 d after mating. (2) eCG (n = 32): Llamas were given 5 mg luteinizing hormone (LH) (Day 0) to induce ovulation, 1000 IU eCG on Day 2, a luteolytic dose of prostaglandin F2α on Day 6, mating on Day 7, and embryo collection on Day 14. (3) eCG+MPA (n = 34): Llamas were treated as those in the eCG group, but a sponge containing 60 mg MPA was placed intravaginally from Days 2 to 6. Llamas that did not respond to synchronization or superstimulation were excluded, leaving data from n = 26, 26, and 27 in the control, eCG, and eCG+MPA groups, respectively, for statistical analysis. The mean (±SD) number of follicles > 7 mm at the time of mating was greatest in the eCG group, intermediate in the eCG+MPA group, and lowest in the control group (16.6 ± 5.3, 12.9 ± 3.7, and 1.0 ± 0.0, respectively, P < 0.001). The number of corpora lutea was similar between eCG and eCG+MPA groups (10.1 ± 2.9 and 8.6 ± 3.7, respectively); both were higher (P < 0.001) than in controls (0.9 ± 0.3). The number of embryos did not differ significantly between the eCG and eCG+MPA groups (4.8 ± 2.8 and 3.5 ± 3.0, respectively), but both were higher (P < 0.001) than in the controls (0.7 ± 0.4). In conclusion, eCG, with or without MPA effectively induced a superovulatory response and multiple embryo production in llamas.